Pada Masa Khalifah Umar Bin Khatab : Kemajuan Islam Sebagai Kekuatan Politik - Rohadi; Muhammad Fitriyadi (Hikamatzu | Journal of Multidisciplinary, 2024)
This research aims to analyze the period of Caliph Umar Bin Khatab: the progress of Islam as a political force. type of research literature study. Data collection with documentation. Analysis with SLR. Umar Bin Khattab was one of the intelligent companions of the Prophet, who had concrete implications when he was appointed second caliph. Umar understands that legal verses are not textual but makes contextualization efforts in understanding Islamic teachings and taking essential meanings that focus on the maslahah aspect. Many policies resulting from ijtihad during his leadership were considered controversial, especially in the legal field. In the field of government, Umar was a reformer and pioneer in aspects of management and administration who became a source of inspiration for the government systems of Muslims and nations in the world.